2015
DOI: 10.1007/s10803-015-2530-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Standardized Equine-Assisted Therapy Program for Children with Autism Spectrum Disorder

Abstract: In this study the effectiveness of an equine-assisted therapy (EAT) in improving adaptive and executive functioning in children with autism spectrum disorder (ASD) was examined (children attending EAT, n = 15, control group n = 13; inclusion criteria: IQ > 70). Therapeutic sessions consisted in structured activities involving horses and included both work on the ground and riding. Results indicate an improvement in social functioning in the group attending EAT (compared to the control group) and a milder effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
1
38

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(196 citation statements)
references
References 36 publications
4
153
1
38
Order By: Relevance
“…The above anecdotal evidence might cause researchers to avoid recruitment of individuals with ASD and IDD to research projects due to the difficulty in obtaining consistent, reliable results. For example, a recent research examining equine-assisted therapy for children with ASD, had an inclusion criteria of IQ performance above 70 and verbal abilities, due to the demands of attention and focus required for sessions [74]. The exclusion of this group would be unfortunate in light of findings indicating improvements in motor abilities, self-concept, autonomy and social integration and well-being in this group of clients [70,[75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…The above anecdotal evidence might cause researchers to avoid recruitment of individuals with ASD and IDD to research projects due to the difficulty in obtaining consistent, reliable results. For example, a recent research examining equine-assisted therapy for children with ASD, had an inclusion criteria of IQ performance above 70 and verbal abilities, due to the demands of attention and focus required for sessions [74]. The exclusion of this group would be unfortunate in light of findings indicating improvements in motor abilities, self-concept, autonomy and social integration and well-being in this group of clients [70,[75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Bu tür gelişimlerin farklı bir hastalık türü olan otizm spektrum bozukluğunda da gözlene-bileceği belirtilmiştir. 26 Borgi ve arkadaşları, terapötik ata binme aktivitesinin OSB'li çocuklardaki toplumsal işlevler ve motor yetenekler üzerine etkilerini incelemişlerdir. Araştırmacılar toplumsal işlev ve motor yetenekleri ölçmek için Vineland Adaptif Davranış Ölçeğini kullanmışlardır.…”
Section: Discussionunclassified
“…Araştırma sonucunda terapötik ata binme aktivitesinin toplumsal işlev düzeyinde ciddi bir artış ve motor yeteneklerde orta düzeyde bir artış sağladığını bulunmuştur. 26 Araştırmamız sonucunda da benzer sonuçlar bulunmuştur. Terapö-tik ata binmenin OSB'li çocuklarda yaşam kalitesi üzerine etkisini inceleyen bir çalışmada, aktivite öncesi ve sonrası sonuçlar değerlendiril-diğinde çocukların toplumsal, fiziksel ve okulla ilişkili yaşam kalitesinde artış saptanmıştır.…”
Section: Discussionunclassified
“…In a recent study by Borgi et al [40] who assessed structured activities in the presence of horses, done both on the ground and while riding the horses, showed that equine-assisted therapies (EAT)-improved social functioning, mildly motor abilities, and executive functioning. Similarly, Lanning et al [41] demonstrated that equine assisted activities can help improve physical, emotional, and social functioning which correlates to the work of Ajzenman et al [42] who found that hypnotherapy can help decrease postural sway and improve adaptive behaviors, which is receptive communication and coping, participation in self-care, low-demand leisure, and social interactions.…”
Section: Manipulative and Body-based Practicesmentioning
confidence: 99%